Assessing Mangrove Healthiness Level of Mangroves Along the Oesapa Coastline Using the MonMang App - Muhammad Soimin (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
Despite being considered one of the most important ecosystems on earth, mangrove forests have been threatened by humans, which can lead to global mangrove loss. Therefore, the restoration of mangroves on both a global and a certain spatial scale is required. One of the mangroves that benefit local communities ecologically is occurring along the Oseapa coastline in Kupang, East Nusa Tenggara Province. In order to successfully restore degraded mangroves, a comprehensive assessment of their healthiness level is necessary. Hence, the MonMang Android-based application developed by BRIN can be used to collect the data within observation transects and plots and then analyze the healthiness level. The Oesapa mangrove forest is a habtat for 8 mangrove species belonging to 5 families. They are Avicennia alba, Avicennia marina, Ceriops tagal, Lumnitzera racemosa, Sonneratia alba, Rhizopora mucronata, Rhizopora apiculata, and Xylocarpus sp. The MonMang application reveals that the overall mangrove healthiness is at Moderate level. In addition, we found that Site 2 has the lowest Mangrove Health Index (MHI) value, with an average of 35.00-65.00. This indicates that the reforestation is strongly suggested in this area. It can be prioritized for restoration efforts to improve healthiness and mangrove cover. The spatial re-plantation also needs to be conducted in other locations within Oesapa mangrove forest which possess Moderate level of mangrove healthiness. Moreover, stump occurrence and garbage coverage vary across the observation sites. Site 2 has the highest proportion of stump occurrence, possibly due to past mangrove dieback. Garbage coverage varies across the sites, with plots closest to seaward having the lowest coverage and those close to settlements having the highest. These findings highlight the need for further restoration efforts to maintain the sustainability of mangrove forest along the Oesapa coastline.